Viability of bacterial spores and crack healing in bacteria-containing geopolymer - Jadhav, Umesh U. (2020)
Geopolymer is an emerging alternative green binder to Portland cement. Geopolymer is often more brittle and thus it is highly desirable to impart self-healing into geopolymer. Unlike Portland cement concrete, self-healing through hydration of cement, and leaching and carbonation of hydration products are not feasible in geopolymer. Microbially induced carbonate precipitation (MICP)-enabled sealing is therefore a potential way to engage self-healing in geopolymer. Using Sporosarcina pasteurii as a model MICP bacterium, this paper investigated viability of bacterial spores in a metakaolin-based geopolymer and crack healing in bacteria-containing geopolymer. Spores of S. pasteurii were added into geopolymer mix directly without encapsulation or immobilization. Results showed that bacterial spores did not leak out from the geopolymer matrix and the spores remained viable in the metakaolin-based geopolymer. Cracks in bacteria-containing geopolymer were sealed with CaCO3 after conditioning in precipitation medium for 3 days, which suggests bacterial spores remain viable. The microstructure of metakaolin-based geopolymer is controlled by Si/Al, Na/Al, and H2O/Na2O molar ratio and less depend on age, which allows direct addition of bacteria into geopolymer mix without encapsulation or immobilization to engage MCP-induced self-healing in geopolymer.